Stethoscopes as potential intrahospital carriers of pathogenic microorganisms - Campos-Murguía, Alejandro; León-Lara, Ximena; Muñoz, Juan M.; Macías, Alejandro E.; Álvarez, José A. (American journal of infection control, 2014)
Stethoscopes can take part in the transmission of health care-associated infections. We cultured 112 stethoscopes by direct imprint on blood agar to estimate the prevalence of potentially pathogenic microorganisms. Forty-eight (47%) produced 50 potentially pathogenic microorganisms; from these, 43 (86%) were Staphylococcus aureus, of which 18 (42%) were methicillin-resistant S. aureus. We concluded that stethoscopes should be considered as potential fomites and must be disinfected routinely before and after each patient contact.